Event-Driven Business Solutions: Today's Revolution in Business and Information Technology. - Steinbart, Paul John; Boatsman, James R. (The Accounting Review, 1994)
Reviews the book `Event-Driven Business Solutions: Today's Revolution in Business and Information Technology,' by Eric L. Denna and colleagues.